Estimating the sound transmission loss of a single partition using vibration measurements. (1st December 2018) - Robin, Olivier; Berry, Alain
Abstract: The sound transmission loss of a homogeneous, isotropic, thin panel under a diffuse acoustic field excitation is derived from a measurement of its airborne induced vibration field. Using this single dataset, the virtual fields method allows identifying the wall pressure field exciting the panel and estimating the corresponding incident acoustic power, provided that the differential operator governing the plate dynamics and its material properties are known a priori . Using the same dataset, the radiated acoustic power is calculated using the radiation resistance matrix method. For an aluminium plate, a comparison of transmission loss values obtained using this approach and a standardized measurement shows good agreement off resonance but large discrepancies on resonance and close to resonance, due to ill conditioning of the virtual fields method. A simple correction is proposed on resonance.